2004
DOI: 10.1176/appi.ps.55.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple-Family Groups for Outpatients With Schizophrenia on Caregivers' Distress and Resources

Abstract: Multiple-family group treatment reduced caregivers' distress but did not increase caregivers' resources relative to standard psychiatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 28 publications
2
55
0
3
Order By: Relevance
“…In terms of positive family outcomes, Magliano et al 154 found that family members receiving the family psychoeducation intervention reported increased perceptions of professional and social support. Hazel et al 155 reported caregiver outcomes from the study conducted by the Dyck et al 153 and found that caregivers involved in the multiple family group intervention reported lower levels of distress relative to those involved in standard outpatient treatment.…”
Section: Family-based Servicesmentioning
confidence: 99%
“…In terms of positive family outcomes, Magliano et al 154 found that family members receiving the family psychoeducation intervention reported increased perceptions of professional and social support. Hazel et al 155 reported caregiver outcomes from the study conducted by the Dyck et al 153 and found that caregivers involved in the multiple family group intervention reported lower levels of distress relative to those involved in standard outpatient treatment.…”
Section: Family-based Servicesmentioning
confidence: 99%
“…14,15 McFarlane's MultiFamily Group (MFG) treatment is a behavioral family treatment that combines psychoeducation and skills training 16 ; MFG has been shown to lower relapse rates, improve social functioning, and decrease caregiver burden relative to customary care. [17][18][19][20][21] Only 1 previous study 18 of MFG has demonstrated improved adherence in patients with schizophrenia. Although MFG has features compatible with a cultural perspective, 22 we decided to test a cultural adaptation of the MFG that integrates throughout treatment the role of the sociocultural worlds of this largely immigrant Mexican-origin community.…”
mentioning
confidence: 98%
“…Relative to SFP approaches, MFGT compares favorably in reducing psychiatric relapse and increasing functional outcomes (McFarlane, Link, Dushay, Marchal, & Crilly, 1995;McFarlane, Lukens, et al, 1995). When compared to a standard care group, MFGT has shown reductions in negative symptoms, inpatient service utilization, and caregiver distress in an outpatient community mental health setting (Dyck et al, 2000;Dyck, Hendryx, Short, Voss, & McFarlane, 2002;Hazel et al, 2004;McDonell, Short, Hazel, Berry & Dyck, 2006). As a result of this empirical support of family psycho-education in general, and MFGT the format specifically, MFGT is currently being disseminated throughout the United States through the Substance Abuse and Mental Health Administration's (SAMHSA; 2003) Toolkit for Empirically Supported Treatments.…”
mentioning
confidence: 99%